2021
DOI: 10.3390/s21165636
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights into the Measurement of Carbon Dioxide Concentrations for Clinical Practice in Respiratory Medicine

Abstract: In the field of respiratory clinical practice, the importance of measuring carbon dioxide (CO2) concentrations cannot be overemphasized. Within the body, assessment of the arterial partial pressure of CO2 (PaCO2) has been the gold standard for many decades. Non-invasive assessments are usually predicated on the measurement of CO2 concentrations in the air, usually using an infrared analyzer, and these data are clearly important regarding climate changes as well as regulations of air quality in buildings to asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…The percentage of time without an interpretable PetCO 2 signal was higher than that previously reported in older children by Paruthi et al 6 and similar to that found by Kirk et al 4 Our study is the first to focus on children under 3 years of age. We found that the loss of the than for PetCO 2 is as expected with these techniques 7 and is in agreement with what was described during PSG in children. 3 We think that the difference in interpretable time between the two sensors has determined this lack of concordance detected in our patients during the sleep study.…”
supporting
confidence: 92%
“…The percentage of time without an interpretable PetCO 2 signal was higher than that previously reported in older children by Paruthi et al 6 and similar to that found by Kirk et al 4 Our study is the first to focus on children under 3 years of age. We found that the loss of the than for PetCO 2 is as expected with these techniques 7 and is in agreement with what was described during PSG in children. 3 We think that the difference in interpretable time between the two sensors has determined this lack of concordance detected in our patients during the sleep study.…”
supporting
confidence: 92%
“…In this population, the correlation (R = 0.62), mean bias (13.9 mmHg) and limits of agreement (-5.6-33.6 mmHg) between the measurements provided by the 2 techniques did not suffice to render them interchangeable. Conversely, the values provided by measurement of PtcCO 2 were better correlated with PaCO 2 (R = 0.97), mean bias (1.7 AE 3.9 mmHg) and limits of agreement (-5.8-9 mmHg), which were more compact and closer to those recommended by the American Association for Respiratory Care (1.96 AE 7.5 mmHg) [46]. Present-day limitations to widespread utilization of PtcCO 2 technology stem from its high cost, its uneven availability, a need for regular calibration and an incompressible time lapse (a few minutes) between its installation on a patient's skin, and complete calculation of a value [46].…”
Section: Expert Opinion (Strong Agreement)mentioning
confidence: 58%
“…Argumentation: As regards the recommendation of systematic monitoring of etCO 2 during thrombectomy under sedation, it is essentially based on the contribution of this technique to the reduction of per-procedure episodes of desaturation and hypoxemia; this was illustrated in 2 meta-analyses [42,43]. Over recent years, etCO 2 monitoring has been substantially improved [44][45][46], and it now ensures reliable surveillance of respiratory frequency and early detection of hypoventilation episodes in spontaneously breathing patients. In these situations, however, non-invasive evaluation of PaCO 2 by etCO 2 is neither reliable nor precise; moreover, it is influenced by supplemental oxygen flow rates, contamination by atmospheric air, and preferential ventilation of dead space in patients suffering from chronic respiratory disease [44,45,47].…”
Section: Expert Opinion (Strong Agreement)mentioning
confidence: 99%
“…Transcutaneous carbon dioxide (PtcCO 2 ) measures CO 2 that has diffused through a heated area of skin. 21 Since PtcCO 2 may overestimate PaCO 2 , 32 , 50 its main utility may be to track trends rather than determine actual PaCO 2 .…”
Section: Resultsmentioning
confidence: 99%